Frequency and voltage regulation control strategy of Wind Turbine based on supercapacitors under power grid fault - Zhongliang Li; Fang Liu (Energy Reports, 2023)
As the penetration rate of wind turbines gradually increases, the fluctuation of system voltage and frequency significantly increases under power grid fault. In severe cases, wind turbines will disconnect from the grid, leading to large-scale power outages. In order to improve the stability of wind turbine grid connection, a large number of literature has studied the frequency and voltage regulation strategies. However, the existing fault ride through control methods mainly solve the problem of reactive power support during faults, while frequency regulation schemes focus on the frequency changes caused by load fluctuations. There is little research on methods that simultaneously consider voltage ride through and frequency regulation under power grid fault. This paper proposes a voltage and frequency regulation control strategy of wind turbines based on supercapacitors to address the above issues. By switching the functional modes of the energy storage device at different stages, wind turbines achieve the fault through and frequency recovery, thereby enhancing the fault tolerance ability. In the strategy, control process is divided into power grid fault period and fault recovery stage, and it adjusts the auxiliary priority level of energy storage devices based on the electrical response degree of different stages. During the fault, energy storage device is in voltage regulation stage because the voltage drop degree is greater than the frequency fluctuation, and it can ensure the wind turbine does not run off the grid by providing dynamic reactive power support to power grid. In the fault recovery stage, energy storage device is in the frequency regulation stage because of the large frequency deviation, it output active power to accelerate the system frequency recovery rating. Finally, the effectiveness of the control strategy proposed in this paper is verified through simulation.